APLIKASI E-VOTING PEMILIHAN KETUA BEM DI UNIVERSITAS SAHID SURAKARTA - M.Bagus Anan Alvian (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2020)
Sahid University Surakarta is a university which located in Jl. Adi Sucipto No.154, Jajar, Laweyan, Surakarta, Central Java. The Student Executive Board (BEM) is an intra-campus student organization and executive organization in university. In recording of voting election from BEM leader, it is conducted manually and has several weaknesses. This study aims to design and implementan e-voting application in the election of BEM leader at Sahid Surakarta University. System design method based on OOAD (Object Oriented Analysis and Design) while the data collection methods cover observation, interviews, and literature review. The software development procedure uses the waterfall model. The procedure of development consists of need analysis, design, coding, testing, and implementation. Meanwhile, the research respondent were 30 students of informatics engineering at Sahid Surakarta University. The rulests of this study show that (1) evoting application for the election of BEM leader at Sahid Surakarta University has the method of results report on the election, the details of the candidates and the candidate pair, open and close voting. Besides, there are features of the voter export, election period and voting results analyzing (2) the application of e-voting runs 100% with no errors in the functional aspects. Moreover, in the aspects of user testing with the survey method, the total value obtained an average of 3.35 with interpretation strongly agrees to the system anf tools.